The Effect of Galvanic Vestibular Stimulation on Visuospatial Cognition in an Incomplete Bilateral Vestibular Deafferentation Mouse Model - Nguyen, Thanh Tin; Nam, Gi-Sung; Han, Gyu Cheol; Le, Chuyen; Oh, Sun-Young (Frontiers in Neurology, 2022)
Objectives: To investigate the efficacy of galvanic vestibular stimulation (GVS) for recovering from the locomotor and spatial memory deficits of a murine bilateral vestibular deafferentation (BVD) model. Methods: Thirty-six male C57BL/6 mice were allocated into a control group and two experimental BVD groups, with (BVD_GVS group) and without (BVD_non-GVS group) the GVS intervention. We used the open field, Y maze, and Morris water maze (MWM) tests to assess locomotor and cognitive behavioral function before (baseline) and 3, 7, and 14 days after surgical bilateral labyrinthectomy. For the GVS group, a sinusoidal current at the frequency at 1 Hz and amplitude 0.1 mA was delivered for 30 minutes daily from postoperative day (POD) 0 to 4 via electrodes inserted subcutaneously close to both bony labyrinths. Results: Short-term spatial memory was significantly impaired in bilaterally labyrinthectomized mice (BVD_non-GVS group), as reflected by decreased spontaneous alternation performance in the place recognition test and time spent in the novel arm and increased same arm return in the Y-maze test, compared with the control. Long-term spatial memory was also impaired, as indicated by a longer escape latency in the hidden platform trial and lower percentage of time spent in the target quadrant in the probe trial of the MWM. GVS application significantly accelerated the recovery of locomotion and short-term and long-term spatial memory deficits in the BVD mice. Conclusions: Our data demonstrate that locomotion, short-term, and long-term (at least 2 weeks) spatial memory were impaired in BVD mice. The early administration of sinusoidal GVS accelerated the recovery of those locomotion and spatial memory deficiencies. GVS could be applied to patients with BVD to improve their locomotion and vestibular cognitive functioning.